Legal Framework Publication of State Secrets via Cyberspace in Indonesia - Pratama, Yasir Adi (Fakultas Hukum Universitas Lampung, 2023)
The issue of publishing information and electronic data that fall under the category of state secrets via cyberspace remains unregulated in Indonesia, leading to a complex debate between the state's secrecy and the public's right to access information. This tension has been further intensified by the Fourth Industrial Revolution and the widespread availability of information, making it difficult to distinguish between state secrets and public information. As a result, individuals or entities who disseminate state secrets through cyberspace may not be held accountable unless specific regulations are established. This study adopts a normative juridical approach with a legal and conceptual framework to examine the intersection of state secrets and the publication of information through cyberspace, examining relevant provisions from existing laws and regulations. The study's findings may provide the legal vacuum concerning the criminalization of individuals who have published information or electronic information that may be categorized as state secrets through cyberspace..